Predicting the intensity for performing supramaximal incline treadmill interval training in distance runners - Ferley, D. D.; Vukovich, M. D. (The Journal of Strength and Conditioning Research, 2019)
Recent evidence highlights the effectiveness of 30-second bouts paired with level-grade supramaximal interval training (SMIT) and incline treadmill training (INC), respectively, in distance runners. Although INC has been described as a form of SMIT, no investigation of INC involving a supramaximal intensity and 30-second bouts has occurred; hence, no established recommendation for prescribing a supramaximal intensity with 30-second bouts for INC exists. Therefore, the purpose of this investigation included reporting on the time-to-exhaustion (Tmax) response and test-retest reliability of running on a 5% grade using supramaximal intensities of 110, 115, 120, 125, and 130% of the velocity associated with maximum oxygen consumption (Vmax). Additionally, these measures were assessed during 140% Vmax and 1% grade. A second aim included determining the %Vmax associated with a 30-second effort via bivariate analysis. Twelve distance runners (age, 26.9 ± 4.8 years; body mass, 69.2 ± 11.7 kg; height, 177.3 ± 10.2 cm; and VO2max, 61.4 ± 6.3 ml/kg·min) completed 2 Tmax trials at each intensity for measures of reliability. The dependent variable was the Tmax of each condition. Statistical significance was set to p = 0.05. Student's t-test revealed no significant differences between trials for all intensities. One-way analysis of variance revealed (a) that Tmax during INC at 110% Vmax was significantly different than all conditions except 115% Vmax and (b) no significant difference in Tmax between 120, 125, 130, and 140% Vmax conditions. In conclusion, Tmax of all conditions proved reliable, and bivariate analysis revealed running at 125% Vmax on a 5% grade yielded a 30-second effort.